1986
DOI: 10.1177/34.12.2431031
|View full text |Cite
|
Sign up to set email alerts
|

Two-color flow-cytometric analysis of the growth cycle of Plasmodium falciparum in vitro: identification of cell cycle compartments.

Abstract: A previous study (Hare JD, Bahler DW: J Histochem Cytochem 34:215, 1986) has shown that the flow cytometric analysis of acridine-orange-stained Plasmodium falciparum growing in vitro generates a complex two-color display, regions of which correlate with the major morphological stages. In this report, four cell cycle compartments (A-D) are defined by characteristic ratios of red and green fluorescence of cells distributed throughout the erythrocytic cycle as well as by the differential effects of several metabo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

1992
1992
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 0 publications
0
15
0
Order By: Relevance
“…Several groups have tried to infer the life cycle stage of the malaria parasite based on their cytometry data resulting from AO staining (Hare, 1986; Hare and Bahler, 1986; Shapiro and Mandy, 2007). Theoretically, this is possible because the ring stages generally do not express much RNA and have no DNA synthesis so they should fluoresce exclusively green.…”
Section: Single Stains For Determining Malaria Parasitemiamentioning
confidence: 99%
“…Several groups have tried to infer the life cycle stage of the malaria parasite based on their cytometry data resulting from AO staining (Hare, 1986; Hare and Bahler, 1986; Shapiro and Mandy, 2007). Theoretically, this is possible because the ring stages generally do not express much RNA and have no DNA synthesis so they should fluoresce exclusively green.…”
Section: Single Stains For Determining Malaria Parasitemiamentioning
confidence: 99%
“…In the case of malaria research, methods of sorting have already been developed to specifically deal with these kinds of samples (cultivated or short terms cultivated parasites) [9,14,24,25]. These methods could, in principle, also be adapted to perform single cell genotyping.…”
Section: Discussionmentioning
confidence: 99%
“…Cytometry of malaria-infected RBC has been used for (i) monitoring of infected RBC, mainly in mouse models (34)(35)(36)(37)(38)(39), (ii) characterization of infected RBC (15), (iii) assessment of maturation and/or viability of parasites in infected RBC (10,13,14,16,17,40,41), and (iv) to detect and count P. falciparum infected RBC in culture (14,(42)(43)(44) or from patient blood (45)(46)(47), with the possibility to distinguish species based on base composition (2,10,11).…”
Section: Malaria and Flow Cytometrymentioning
confidence: 99%
“…By 1987, it had been shown that flow cytometry of DNA and RNA content of iRBCs could differentiate stages and, in some cases, species (10,11). Flow cytometry has since been used to study parasite physiology and response to antimalarial drugs (12)(13)(14)(15)(16)(17).…”
mentioning
confidence: 99%